2021
DOI: 10.1080/17457300.2021.1942923
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Roadside Design Compliance and Hazard Offset on the Risk of Single-Vehicle, Run-Off-Road Crash Fatalities

Abstract: single-vehicle, run-off-road (sVROR) crashes account for a significant portion of all road-related injuries and fatalities worldwide. however, no previous study has examined to what extent roadside design guidelines have been applied, nor (and most importantly) whether having a compliant roadside design reduces the likelihood of fatal injury occurrence in sVROR crashes. thus, the objectives of this research are i) to examine the level of roadside design compliance within the studied area based on the selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Many of these rollover events occurred after vehicles hit curbs. Previous studies showed that a significant portion of the roadside design adopted in the Emirate of Abu Dhabi is non-compliant to state-ofthe-art guidelines largely due to excessively high curbs [78], which may likely have contributed to vehicle instability, eventually resulting in rollovers; and (ix) crashes occurred at signalized intersections rather than at roundabouts. Indeed, the odds of fatal injury occurrence was found to be 1.8 times higher at signalized intersections as compared to roundabouts while controlling for the presence of access points, lighting condition, object struck, and seatbelt usage, though this finding is based on a p-value marginally higher than the widely used 0.10 threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these rollover events occurred after vehicles hit curbs. Previous studies showed that a significant portion of the roadside design adopted in the Emirate of Abu Dhabi is non-compliant to state-ofthe-art guidelines largely due to excessively high curbs [78], which may likely have contributed to vehicle instability, eventually resulting in rollovers; and (ix) crashes occurred at signalized intersections rather than at roundabouts. Indeed, the odds of fatal injury occurrence was found to be 1.8 times higher at signalized intersections as compared to roundabouts while controlling for the presence of access points, lighting condition, object struck, and seatbelt usage, though this finding is based on a p-value marginally higher than the widely used 0.10 threshold.…”
Section: Discussionmentioning
confidence: 99%